Chronically Elevating Circulating Ketones Can Reduce Cardiac Inflammation and Blunt the Development of Heart Failure. (June 2020) - Byrne, Nikole J.; Soni, Shubham; Takahara, Shingo; Ferdaoussi, Mourad; Al Batran, Rami; Darwesh, Ahmed M.; Levasseur, Jody L.; Beker, Donna; Vos, Dyonne Y.; Schmidt, Mya A.; Alam, Abrar S.; Maayah, Zaid H.; et al.
Abstract : Background: Previous studies have shown beneficial effects of acute infusion of the primary ketone body, β-hydroxybutyrate, in heart failure (HF). However, whether chronic elevations in circulating ketones are beneficial remains unknown. Methods: To chronically elevate circulating ketones in mice, we deleted the expression of the ketolytic, rate-limiting-enzyme, SCOT (succinyl-CoA:3-ketoacid-CoA transferase 1; encoded by Oxct1 ), in skeletal muscle. Tamoxifen-inducible skeletal muscle-specific Oxct1 Muscle− / − knockout (n=32) mice and littermate controls (wild type; WT; n=35) were subjected to transverse aortic constriction (TAC) surgery to induce HF. Results: Deletion of SCOT in skeletal, but not cardiac muscle resulted in elevated concentrations of fasted circulating β-hydroxybutyrate in knockout mice compared with WT mice ( P =0.030). Five weeks following TAC, WT mice progressed to HF, whereas knockout mice with elevated fasting circulating ketones were largely protected from the TAC-induced effects observed in WT mice (ejection fraction, P =0.011; mitral E/A, P =0.012). Furthermore, knockout mice with TAC had attenuated expression of markers of sterile inflammation and macrophage infiltration, which were otherwise elevated in WT mice subjected to TAC. Lastly, addition of β-hydroxybutyrate to isolated hearts was associated with reduced NLRP3 (nucleotide-binding domain-like receptor protein 3)-inflammasome activation, which has been previously shown to play a role in contributing to HF-induced cardiac inflammation. Conclusions: These data show that chronic elevation of circulating ketones protects against the development of HF that is associated with the ability of β-hydroxybutyrate to directly reduce inflammation. These beneficial effects of ketones were associated with reduced cardiac NLRP3 inflammasome activation, suggesting that ketones may modulate cardiac inflammation via this mechanism. Abstract : Supplemental Digital Content is available in the text.